Soft Switched Multi-Output PWM DC-DC Converter - Rashmi Sharma (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
In this paper, a new soft switched cell that overcomes most of the drawbacks of the normal "hard switched-pulse width modulation" converter is proposed to contrive a new family of soft switched PWM converters. All of the semiconductor devices in this converter are turned on and off under exact or near zero voltage switching (ZVS) and/or zero current switching (ZCS). No additional voltage and current stresses on the main switch and main diode occur. A push-pull converter equipped with the proposed snubber cell is analyzed in detail. The predicted operation principles and theoretical analysis of the presented converter are verified with a prototype of a 50W PWM push-pull multi-output converter with insulated MOSFET and for regulation of slave outputs magnetic amplifier post regulators are considered as post regulators. Moreover; this multioutput converter has a simple structure, low cost, and ease of control circuitry.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.4024